A Review of the Therapeutic Properties of Clostridium Botulinum Toxins - Neyazi, Abdul Jawid (Journal of Natural Sciences – Kabul University, 2023)
Clostridium botulinum is an important pathogenic agent that produces seven types of neurotoxins (A-G) and causes severe and fatal disease in different hosts including humans. Beside its pathogenesis, recent studies shows the effectiveness of these toxins for treatment of many disorders of humans in low doses. In this review article, the latest published scientific articles about effectiveness of the mentioned bacterial toxins in the treatment of some specific conditions in humans have been reviewed and their specific results have been used. The results of various studies show that in addition to the severe and lethal properties of Clostridium botulinum toxins, a number of these toxins, especially type A and B (especially Botox) have wide therapeutic uses and, is used for the treatment of various disorders in humans, which is cheap, safe and effective compared to other methods, and it is easy to apply.